The Importance of Coordinated Actions in Preventing the Spread of Yellow Fever to Human Populations: The Experience from the 2016-2017 Yellow Fever Outbreak in the Northeastern Region of São Paulo State. (19th May 2019) - Siconelli, Márcio Junio Lima; Espósito, Danillo Lucas Alves; Moraes, Nathália Cristina; Ribeiro, Julia Maria; Perles, Lívia; Dias, Maria Angélica; Carvalho, Adolorata Aparecida Bianco; Werther, Karin; Fernandes, Natália Coelho Couto de Azevedo; Iglezias, Silvia D'Andretta; Bürger, Karina Paes; Fonseca, Benedito Antonio Lopes da
Abstract : Yellow fever (YF) is a zoonotic arthropod-borne disease that is caused by the yellow fever virus (YFV) and characterized by a sylvatic and urban cycle. Its most severe presentation is manifested as a hemorrhagic disease, and it has been responsible for thousands of deaths in the last decades. This study describes the public health approaches taken to control the 2016-2017 YF outbreak in nonhuman primates (NHPs) that took place in the northeastern region of São Paulo state, Brazil. NHPs recovered from the field were necropsied, and YF diagnoses were made at the Laboratory of Molecular Virology, Ribeirão Preto Medical School and the Center of Pathology, Adolfo Lutz Institute of São Paulo. NHP samples were inoculated into Vero cells for YFV isolation. RNA extraction was performed directly from NHP tissues and tested by RT-qPCR. YFV-positive samples were confirmed by sequencing. Based on the rapid RT-qPCR results, surveillance actions were implemented in the entire region. Confirmatory histopathology and immunohistochemistry for YFV were also performed. Among nine NHPs, gross hepatic involvement was observed in six animals, five of which were YFV-RT-qPCR-positive. One YFV was isolated from the serum of an infant NHP. YFV RNA sequences diverged from the virus responsible for the last epizootic that occurred in São Paulo state, but it was similar to the current Brazilian epizootic. Public health actions included dissemination of information on YF transmission, investigation of the probable location of NHP infection, characterization of the environment, and subsequent creation of the blueprint from which prevention and control measures were implemented. The YFV sylvatic cycle occurred in the periurban areas of the northeastern region of São Paulo state, but no human cases were reported during this period, showing that integrated actions between human, animal, and environmental health professionals were critical to restrain the virus to the sylvatic cycle.